Weight Bearing CT Analysis of the Transverse Tarsal Joint During Eversion and Inversion. Issue 1 (January 2022) - Jeng, Clifford L.; Rowe, Nicholas; Robertson, Cassandra E.; Singh, Stuti; Campbell, John T.
Category: Basic Sciences/Biologics; Hindfoot Introduction/Purpose: Current understanding of the kinematics of the transverse tarsal joint continues to evolve. Unfortunately, most prior studies have been in cadavers or under non-physiologic conditions. Weight bearing CT scans may provide more accurate in vivo information about the position of the transverse tarsal joint during eversion and inversion. Methods: Institutional Review Board approval was obtained. Five normal volunteers underwent bilateral weight bearing cone- beam PedCAT scans (CurveBeam LLC, Hatfield, PA) while standing on platforms that positioned both hindfeet in 20o of valgus and then 20o of varus. The CT scans had a field-of-view diameter of 350 mm and a field-of-view height of 200 mm. The scan exposure time was 9 seconds, with a total scan time of 54 seconds. The datasets were reconstructed using filtered back projection with 0.37mm isotropic voxels. The resulting volumes were then segmented, identifying the [x, y, z] coordinates that comprised each bone. Each bone of the hindfoot was segmented on the scan images and the motion between the talus and calcaneus was analyzed. A similar analysis was done for motion between the navicular and cuboid. Two-tailed paired Student's t- tests were used to compare the angle and distance measurements between valgus and varus positions. Results: In the coronal plane, the axis of the talus rotated by 17.0° relative to the axis of the calcaneus as the hindfoot moved from eversion to inversion (p=0.03). The distance between the centers of the talar head and the anterior calcaneus also moved closer to each other by 7.1 mm (p=0.00005). There was no significant change in angle or distance between the navicular and cuboid when moving from eversion to inversion. The angle between the navicular and cuboid axes changed 2.1° (p=0.7), while the distance changed 0.8 mm (p=0.7) Conclusion: Previous work proposed that the transverse tarsal joint locking mechanism occurs from the talonavicular and calcaneocuboid joint axes diverging (less parallel) as the hindfoot inverts. The current weight bearing CT data shows that not only do the talar and calcaneal axes rotate relative to each other during inversion, but the center of the talar head and anterior calcaneus translate to move closer together. Because the navicular and cuboid do not move, transverse tarsal joint locking may occur due to tightening of the joint capsules and ligaments. Further in vivo study is warranted, especially under dynamic weightbearing conditions.